Research Status and Prospect for Vibration, Noise and Temperature Rise-Based Effect of Food Transport Pumps on the Characteristics of Liquid Foods - Jia, XiaoQi; Li, Songyu; Li, Bo; Zhang, Li; Ding, Qiangmin; Gao, Panlong; Zhu, ZuChao (Frontiers in Nutrition, 2022)
In the field of food processing, the processing of liquid foods has always played an important role. Liquid foods have high requirements for the processing environment and equipment. As the core equipment in liquid foods processing, food transport pumps are widely used in liquid foods production, processing and transportation. Most liquid foods are non-Newtonian and vulnerable to vibration, noise, and temperature rise produced by rotary motions of food transport pumps in operation, which can finally affect foods safety. Therefore this review summarizes the impact of mechanical vibration, noise, and temperature rise on liquid food products, with the aim of ensuring food safety while designing a cleaner, safer and more reliable food transport pumps in the future.